Topical versus systemic antibiotics for chronic suppurative otitis media - Chong, L; Head, K; Richmond, P; Snelling, T; Schilder, A; Burton, M; Brennan-Jones, C (Wiley, 2018)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To assess the relative effectiveness of topical versus systemic antibiotics for people with chronic suppurative otitis media (CSOM).